Errors in organizations: the impact of error orientation on work-related personal development - Fischer, Isabelle (2021)
Successfully implemented error management practices help to improve the overall company performance and furthermore increase learning and exploration on the individual level. Moreover, does the construct of error orientation refer to the way how individuals cope with and think about errors at work. Since every organization is confronted with errors, it is essential to manage them actively and take advantage of their positive consequences in order to foster continuous learning and development within an organization. This research, which is based on the data collected through a survey among 209 international employees, revealed that error orientation is indirectly related to job crafting through its relationship with personal growth initiative. Furthermore, the leadership functions of providing feedback, training and developing the team, challenging the team as well as supporting a social climate, have a negative effect on the relationship of error orientation on personal growth initiative. Lastly, it shows that the mediation of personal growth initiative on the relationship between error orientation and job crafting exists especially when the latter leadership functions are low.